Incidence and Patterns of Major Complications Following Spinal Instrumentation- A Retrospective Descriptive Study from a Tertiary Care Center in Nepal - Munakomi, Sunil; K.C., Saugat; Chaulagain, Dipak; Grasso, Giovanni (Eastern Green Neurosurgery, 2022)
Background: With the continuous uprise of spinal instrumentations within the global front, the complications they harbinger may have multispectral effects upon the patients as well as their caretakers. These are of prime significance in the context of low and middle-income nations. There is however drought of studies pertaining to the same in our subcontinent. Materials and methods: A retrospective descriptive study was undertaken to study the incidence and patterns of early and late major complications among 300 patients undergoing spinal instrumentation from the hospital database of the College of Medical Sciences (CMS), in Bharatpur, Chitwan, Nepal. Results: Trauma comprised 63.33% of cases in the study. 40% of the study cohorts were either in the American Spinal Injury Association (ASIA) ‘A’ or ‘B’ neurological status. The incidence of major complications in our study cohort was 20.33%. The posterior-only surgical approach was undertaken in 200 (66.67%). Surgical site infection was the most common type of complication observed (6.67%). Hardware-related complications were observed in 5.67%) of cases. The incidence of re-operation was 2.67%. The mortality rate observed in our study was 2%. Conclusion: Adequate preoperative planning, proper optimization of the patient, and adoption of procedure-specific, risk-adjusted predictive models may be pivotal for nullifying complications adherent to spinal instrumentation.